A distributed framework for health information exchange using smartphone technologies - Abdulnabi M.; Al-Haiqi A.; Kiah M.L.M.; Zaidan A.A.; Zaidan B.B.; Hussain M. (Academic Press Inc., 2023)
Bioinformatics; Computer operating systems; Computer peripheral equipment; Digital storage; Health; Health care; Hospital data processing; Information dissemination; Interoperability; Medical computing; Mobile computing; Smartphones; Design and operations; Distributed framework; Distributed storage; Health care providers; Health information exchanges; Health information systems; mPHR; Personal health record; mHealth; Article; computer interface; electronic patient record; human; medical information system; medical technology; mobile application; priority journal; smartphone; electronic medical record system; medical record; Health Information Exchange; Health Records, Personal; Humans; Medical Records Systems, Computerized; Smartphone